Identifying and Modeling the Participation of Regional Agro-Industrial Sector Producers in Value Chains - Svetlana Eduardovna Soldatova; Ksenia Yurievna Voloshenko (Управленческое консультирование, 2018)
The article considers methodological features of identifying the participation of regional producers in value chains as an effective mechanism to coordinate economic activity within technological cycles. Economic-mathematical model of optimizing interaction and coordination of activities between participants on the criteria of value added maximizing with spanning variables is offered for value chain management applied to regional agro-industrial sector. Specifications of model constraints are related to available resources, proportion of production output in industries and activities in the value chain, conditions for sales, production merchandising and infrastructure developing, technology proportion, production capacity and other requirements. In addition, special attention is given to particular type of model constraint as receiving secure added value in the previous link of value chain.